THE CAPACITY OF LOCAL GOVERNMENTS IN NEPAL - Hari Prasad Adhikari; Moh. Kurdi (PERFORMANCE: Jurnal Bisnis & Akuntansi, 2025)
The capacity of local governments in Nepal is the main emphasis of this study. Using a descriptive research approach, the study analyzed data obtained from 150 respondents who completed questionnaires. The performance of local governments' capacity is at a moderate level, according to the data analysis. The report provides valuable insights into how local governments are currently handling their duties and obligations. Policymakers may find the results useful in creating more effective strategies and regulations to raise the efficiency of local governance in Nepal. The findings of this study can help with initiatives to fortify and enhance local governments' future capabilities.